PENGUJIAN STRUKTURAL PADA MOTIVASI DAN PARTISIPASI MASYARAKAT DALAM PENGANGGARAN DESA - Dekeng Setyo Budiarto; Nuryaningsih Hidayati (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
Participation in village preparation programs is crucial for the community because they are more aware of the conditions and needs in their area. The research explores the impact of leadership style, political legitimacy, village officials' performance on community participation, and the budgeting community motivation in the village. The population of this research is village officials in Seyegan District, Sleman Regency, who are involved in budgeting. The study was conducted for five months and managed to collect 50 respondents. This study uses smart PLS to test several variables in the hypothesis. Hypothesis testing shows that the performance of village officials has an impact on community participation and community participation has an effect on community motivation in budgeting. However, this study cannot prove the influence of leadership style and political legitimacy on community participation in village budgeting.